THEME IN THE VIETNAMESE CLAUSE SIMPLEX: A SYSTEMIC FUNCTIONAL DESCRIPTION - Van, Hoang Van (VNU Journal of Foreign Studies; Vol 38 No 3, 2022)
This article is a functional description of an aspect of textual grammar of Vietnamese. The theoretical framework adopted for the description is Systemic Functional Grammar (SFG) as developed by Halliday and other systemicists. The focus is on the description of Theme in the clause simplex. Two main questions which form the basis of this article are: (1) “what is Theme in the Vietnamese clause simplex and how is it recognised?”; and (2) “what are the delicate options available in the environment of THEME and how are they distinguished?”   The study shows that Theme in Vietnamese is a system of the clause as a message; it can be defined as “the point of departure of the message” (Halliday (1967b, p. 212; 1970, p. 161; 1985b, p. 38), and can be recognized by first position in the clause; and the environment of THEME  opens for a number of delicate options, and these options can be distinguished along the three metafuncions of language: the experiential, the interpersonal, and the textual. The study contributes to the application of SFG theory to the description of textual grammar of the Vietnamese clause, opening up potentials for a new approach to the description of a comprehensive SFG of Vietnamese for language teaching, learning, and research.